(untitled) (Nigerian Journal of Technology, 2017)
This study investigated the possibility of separating oil palm kernel and shell mixture using media other than clay in wet separation. The separation efficiency of each medium ["Ikwube" (anthill), palm ash and sandy loam soil] was compared with that of clay. The effect of media type, specific gravity of the slurry, pH and slurry viscosity on the efficiency of separation were studied. The media/water ratio of 0.20:1, 0.30:1, 0.40:1, and 0.50:1 by weight were prepared in four aluminum pots for each medium at a time and each used to separate 20kg of cracked nut (palm kernel and shell mixture). The specific gravity and viscosity increases with increase in media/water ratio while the pH decreases. Higher slurry viscosity resulted in a better separation but there is decrease in the efficiency when viscosity is above 3.5 and 5.5 cP for clay and "Ikwube" respectively. The suitable media slurries were found to have specific gravities between 1.04 and 1.12. The optimum condition in which separation efficiency was found in the media/water ratio of 0.30:1. Among the media used, "Ikwube" was found to be comparable to clay at a medium-to-water ratio of 0.30:1 giving 98.93% efficiency. Thus, it is recommended that "Ikwube" can be used in place of clay for wet separation. http://dx.doi.org/10.4314/njt.v36i2.38